Analysis of Articles Published in Journal of Indian Education (2015–2020) - Bankra, Alka (JOURNAL OF INDIAN EDUCATION, 2022)
The Journal of Indian Education is a quarterly periodical published by NCERT in context of Teacher Education and School Education. Currently, it is on the verge of publishing volume 48, issue 1 against the upcoming May 2022 issue. Several noteworthy and enlightening contributions have already been accounted, speaking of the sparkling glory and success of the journal in the sector of Teacher and School Education. The paper focuses on the thematic reflection of the articles published from February 2015 to November 2020. On summarising, it was found that a sum of 280 articles have been published between the years 2015 to 2020, inclusive of the national and global contributions. The analysis is conducted in terms of demography of the papers, percentage contribution of the categorised partakers, research and analysis methodologies followed in the pursued studies with the discussion on thematic reflections.